PENGARUH SUBSTITUSI TEPUNG BENGKUANG TERHADAP KUALITAS BROWNIES KUKUS - Pratiwi, Novia Utami; Faridah, Anni; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2015)
Yam flour as a food ingredient has not been optimally used in the diversification of food processing. While yam contains inulin that can not be digested by the body and beneficial to health. This study aimed to analyze the influence of yam flour substitution on the quality of color, aroma, texture, taste and preferences steamed brownies. This research is an experiment using a completely randomized design with one factor substitution yam flour (0%, 25%, 50%, 75% and 100%) three times repetition. The data used is primary data obtained directly from the 30 panelists who gives an answer of organoleptic test format. The data has been obtained and tabulated in tables and analysis of variance (ANOVA). If there is then tested the effect of Duncan. The results showed no significant effect of 0%, 25%, 50%, 75% and 100% substitution yam flour on the quality of steamed brownies that the brown color quality Fh (2.26) <Ft (2:47), the quality of the chocolate aroma Fh (0.87 ) <Ft (2:47), chocolate Fh (1.81) <Ft (2:47), sweet taste Fh (0:39) <Ft (2:47) but the effect on the quality of the soft texture Fh (37.01)> Ft (2:47), Overall good value contained in yam flour substitution as much as 25% (X1). The highest yield panelists preferred contained in yam flour substitution as much as 25% (X1). Keywords: yam flour, steamed brownies, brownies quality steamed